What is economic growth and human development influence on poverty in West Sumatra - Putra, Trimardi Jaya; Wirda, Fisla (Trigin Publisher, 2024)
The poverty rate is used as one of the benchmarks for assessing the success of a nation's development. This study aims to determine the effect of economic growth and human development index (HDI) on poverty levels. The data used is secondary data published by the Central Statistics Agency (BPS) of West Sumatra Province from 2010 to 2021 detailed for 19 (nineteen) districts/cities. The number of samples in this study was 228 (two hundred twenty-eight) observations. Data analysis is done by multiple linear analysis of panel data using the help of the Eviews program. The results of the analysis show that the poverty rate is proven to be significantly influenced by economic growth and human development index. Partially, the variable poverty rate is influenced by economic growth in a negative direction, but the effect is not significant. The poverty level variable is also proven to be influenced by the human development index with a significant negative value.